Improve Management of acute heart failure with ProcAlCiTonin in EUrope: results of the randomized clinical trial IMPACT EU Biomarkers in Cardiology (BIC) 18. (12th December 2019) - Möckel, Martin; de Boer, Rudolf A.; Slagman, Anna Christine; von Haehling, Stephan; Schou, Morten; Vollert, Jörn Ole; Wiemer, Jan C.; Ebmeyer, Stefan; Martín‐Sánchez, F. Javier; Maisel, Alan S.; Giannitsis, Evangelos
Abstract : Aim: To determine whether initiation of antibiotic therapy (ABX) by procalcitonin (PCT) within 8 h of admission in patients presenting to the emergency department with symptoms and signs of acute heart failure (AHF) and elevated natriuretic peptides would improve clinical outcomes. Methods and results: The study was a randomized multicentre clinical trial conducted at 16 sites in Europe. Patients were randomized to either a PCT‐guided strategy or standard care. Patients with PCT‐guided strategy ( n  = 370) had ABX initiated if PCT was > 0.2 μg/L. Patients with standard care ( n  = 372) had AHF care in accordance with published guidelines without PCT. The primary endpoint was 90‐day all‐cause mortality. Pre‐specified secondary endpoints included 30‐day all‐cause mortality and readmission and rate of pneumonia. The Data Safety and Review Committee recommended stopping the study for futility when 762 of the planned 792 patients had been enrolled. A total of 742 patients could be analysed. Patients were elderly (median age: 77 years), 38% were women, and had typical signs and symptoms of AHF. All‐cause mortality at 90 days was 10.3% in the PCT‐guided group vs. 8.2% in standard care ( P  = 0.316). Thirty‐day readmission was significantly higher in the PCT‐guided group vs. standard care but the difference vanished until day 90. The rate of pneumonia was overall low (7.5%) and not different between groups. Conclusions: In patients with AHF, a strategy of PCT‐guided initiation of ABX was not more effective than a standard care strategy in improving clinical outcomes.